2003
DOI: 10.1111/j.1939-1676.2003.tb02496.x
|View full text |Cite
|
Sign up to set email alerts
|

M‐Mode Echocardiographic Ratio Indices in Normal Dogs, Cats, and Horses: A Novel Quantitative Method

Abstract: A novel method for quantitative echocardiographic interpretations is introduced based on the calculation of ratio indices in which each raw M-mode measurement is divided by the aortic root dimension (Ao). ''Aorta-based'' indices were calculated with the animal's measured aortic root dimension (Ao m ) as the length standard. Conversely, ''weight-based'' indices employed an idealized estimate of aortic dimension (Ao w ) with a weighted least squares linear regression against the cube root of body weight (Ao w ϭ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
81
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 14 publications
7
81
0
3
Order By: Relevance
“…Several echocardiographic parameters correlated positively to body weight in the three breeds included in the present study, in conformity with earlier reports on other populations (Boon et al, 1983;Lombard, 1984;Jacobs and Mahjoob, 1988;Brown et al, 2003;Kayar et al, 2006). Lonsdale et al (1998) demonstrated the effect of training on the IVSs in English Greyhounds, as this value proved to be significantly higher in trained dogs.…”
Section: Discussionsupporting
confidence: 93%
“…Several echocardiographic parameters correlated positively to body weight in the three breeds included in the present study, in conformity with earlier reports on other populations (Boon et al, 1983;Lombard, 1984;Jacobs and Mahjoob, 1988;Brown et al, 2003;Kayar et al, 2006). Lonsdale et al (1998) demonstrated the effect of training on the IVSs in English Greyhounds, as this value proved to be significantly higher in trained dogs.…”
Section: Discussionsupporting
confidence: 93%
“…Three cardiac cycles were measured and averaged for further analyses. As the study population showed a wide range of BW, the measurements were corrected for differences in weight according to the principles of allometric scaling (Brown et al, 2003;Cornell et al, 2004). Specifically, the measurements of chamber dimensions were normalised to a BW of 500 kg [500] using the following equations:…”
Section: Echocardiographic Examinationmentioning
confidence: 99%
“…An electrocardiogram (ECG) was recorded with a 12-lead computerbased system (ECG-PC, TEB, Brazil) [49]. Echocardiography was performed with a 5 MHz electronic ultrasound probe (EUB-405, Hitachi, Norcross, GA, USA) [13]. …”
Section: Cardiac Evaluationmentioning
confidence: 99%